PELATIHAN DAN PEMBENAHAN MANAJEMEN BISNIS DAN PEMBUKUAN KUPIAH TRADISIONAL PADA PENGRAJIN â€œLILI KOLEKSIâ€ KECAMATAN LUBUK KILANGAN KOTA PADANG - HATTA, ERMATATI; Maretha Rissi, Dita; Haslina, Welsi; Gustati (Jurusan Akuntansi Politeknik Negeri Padang, 2020)
Lili Collection is one of the traditional skullcap craftsmen who are on Jl. Beringin RT 01 / RW 01, Lubuk Kilangan Subdistrict, Padang City since 2009. With the speed of development in the industrial world, this business is experiencing difficulties in developing its business and losing market share. This handicraft business has not carried out financial bookkeeping in accordance with UMKM standards. The purpose of this activity is to help traditional skullcap craftsmen to develop their businesses through training and business management and bookkeeping improvements tailored to this type of business, namely MSMEs. So that the hope of this activity is that it can help partners develop their businesses and gain market share in the eyes of the community through proper business management. What is no less important is the existence of this activity, it is hoped that partners will be able to do financial bookkeeping properly according to the MSME standards. This bookkeeping is useful for partners to know their financial position and make this financial information the basis for future decision making.